Association of PNPLA3 rs738409 polymorphism with liver steatosis but not with cirrhosis in patients with HBV infection: Systematic review with meta‐analysis. (26th January 2018) - Ghalamkari, Saman; Sharafi, Heidar; Alavian, Seyed Moayed
Abstract: Background: Hepatitis B virus (HBV) infection is a worldwide health issue and is well known for being the main cause of developing secondary liver complications such as cirrhosis and hepatocellular carcinoma (HCC). The PNPLA3 rs738409 polymorphism has been investigated conclusively with occurrence risk of steatosis and cirrhosis. Therefore, performing a meta‐analysis of the available studies with the aim of clarifying the association between rs738409 and occurrence risk of steatosis and cirrhosis among HBV‐infected patients would be helpful. Methods: Chronic HBV infection was defined as the persistence of HBsAg for more than 6 months. To gather sufficient data for this meta‐analysis, reliable databases were conclusively searched using appropriate keywords. Only studies that satisfied the inclusion criteria were enrolled in the present study. Results: This meta‐analysis pooled four studies with 1135 cases of chronic hepatitis B (CHB) to evaluate the impact of PNPLA3 SNP on liver steatosis and also pooled five studies with 3713 cases of CHB to evaluate the impact of PNPLA3 SNP on cirrhosis. The association of rs738409 with each complication was investigated. The rs738409 was found to be associated with steatosis in recessive [ p = 4.57 × 10 –6, odds ratio (OR) = 2.85], dominant ( p = 4.35 × 10 ‐6, OR = 1.84), co‐dominant ( p = 6.18 × 10 ‐8 ; OR = 3.74) and allelic ( p = 9.79 × 10 ‐9 ; OR = 1.78) models. No association was found between rs738409 and cirrhosis development in recessive ( p = 0.99, OR = 1.00), dominant ( p = 0.30, OR = 0.92), co‐dominant ( p = 0.74; OR = 0.96) and allelic ( p = 0.45; OR = 0.96) models. Conclusions: Although the PNPLA3 rs738409 G allele has been associated with the risk of steatosis in CHB patients, no association between this polymorphism and the risk of cirrhosis was seen.